2020
DOI: 10.23860/jmle-2020-12-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational food-focused media literacy in Jamaica

Abstract: Media use has been linked to unhealthy eating, but there is evidence that parent discussion about media and media literacy can inoculate against negative media effects. Therefore, we examined the relationships between mothers' food-focused media literacy and their discussions about media and their adolescents' food-focused media literacy in a survey of 82 motheradolescent dyads in Jamaica, a middle-income country where obesity is rising. As expected, mothers' food-focused media literacy was both greater than a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Parental mediation includes how parents limit (restrictive mediation) and/or talk with their child about what they see in media (active mediation) and is typically related to lower screen time and better quality media use (Valkenburg et al, 2013). One study found that over 70% of Black Jamaican mothers in Jamaica report discussing screen time with their adolescents and that the emotional intensity of those parent–adolescent discussions is associated with higher adolescent media literacy (Nelson et al, 2020). However, little work has been done to examine parental mediation in Black American or U.S. immigrant families (Chen & Shi, 2019).…”
Section: Screen Media Behaviors Parent–adolescent Factors and 3d Accu...mentioning
confidence: 99%
“…Parental mediation includes how parents limit (restrictive mediation) and/or talk with their child about what they see in media (active mediation) and is typically related to lower screen time and better quality media use (Valkenburg et al, 2013). One study found that over 70% of Black Jamaican mothers in Jamaica report discussing screen time with their adolescents and that the emotional intensity of those parent–adolescent discussions is associated with higher adolescent media literacy (Nelson et al, 2020). However, little work has been done to examine parental mediation in Black American or U.S. immigrant families (Chen & Shi, 2019).…”
Section: Screen Media Behaviors Parent–adolescent Factors and 3d Accu...mentioning
confidence: 99%